The complete chloroplast genome sequence of Taxus yunnanensis - Yunfen Geng; Yunqin Li; Xiaolong Yuan; Mei Hua; Yi Wang; Jinfeng Zhang (Mitochondrial DNA. Part B. Resources, 2020)
The first complete chloroplast genome (cpDNA) sequence of Taxus yunnanensis was determined from Illumina HiSeq pair-end sequencing data in this study. The cpDNA is 129,190 bp in length. Like other species of taxus genus, the chloroplast genome of T. yunnanensis has lost one of the large inverted repeats (IRs). The genome contains 116 genes, including 82 protein-coding genes, 4 ribosomal RNA genes, and 30 transfer RNA genes. Further phylogenomic analysis showed that T. yunnanensis closed to T. brevifolia in Lauraceae family.